2014
DOI: 10.3791/51686
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of Egyptian Blue and Han Blue, Two Alkali Earth Copper Silicate-based Pigments

Abstract: In a visualized example of the ancient past connecting with modern times, we describe the preparation and exfoliation of CaCuSi 4 O 10 and BaCuSi 4 O 10 , the colored components of the historic Egyptian blue and Han blue pigments. The bulk forms of these materials are synthesized by both melt flux and solid-state routes, which provide some control over the crystallite size of the product. The melt flux process is time intensive, but it produces relatively large crystals at lower reaction temperatures. In compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 21 publications
(18 reference statements)
0
31
0
Order By: Relevance
“…Bulk EB shows a remarkable high quantum yield of 10.5% for a NIR emitter compared with SWCNTs, quantum dots, metal nanoclusters, and FDA-approved fluorophores such as ICG 5,28 . Recently, micrometer-sized monolayer sheets of EB were isolated by stirring in hot water for several days 29,30 . However, the remarkable properties of EB have not been explored for developing NIR luminescent nanomaterials for bioimaging applications.…”
mentioning
confidence: 99%
“…Bulk EB shows a remarkable high quantum yield of 10.5% for a NIR emitter compared with SWCNTs, quantum dots, metal nanoclusters, and FDA-approved fluorophores such as ICG 5,28 . Recently, micrometer-sized monolayer sheets of EB were isolated by stirring in hot water for several days 29,30 . However, the remarkable properties of EB have not been explored for developing NIR luminescent nanomaterials for bioimaging applications.…”
mentioning
confidence: 99%
“…In the second experiment, similar mixtures of brass, SiO 2 and CaCO 3 were heated in the same way but no flux was added and the temperature was raised to 975 °C. The conditions chosen for the second experiment are similar to those proposed in literature for solid-state synthesis (Johnson-McDaniel and Salguero 2014). Once at room temperature, the crucibles of both preliminary experiments were photographed with the Visible Induced Luminescence (VIL) technique to detect the presence of cuprorivaite-like materials formed.…”
Section: Author Accepted Manuscriptmentioning
confidence: 99%
“…Different ground particles were produced, varying in size between 125 and 250 μm. Two experimental methods have recently been reported for the production of the pigment described by Johnson‐McDaniel et al: The melt‐flux method requires lower temperature (875 °C) and produced smaller sized particles in the laboratory (5–15 μm crystallites by SEM), whereas solid state synthesis yielded larger particle sizes (15–50 μm) but requires higher synthesis temperatures (1020 °C), thus above the melting point of bronze. In archaeological studies, Grifa et al demonstrated that high temperatures were achieved in synthesis using crucibles from Cuma, thus exceeding the thermal stability of cuprorivaite crystals (950–1050 °C), thus within the range for both synthesis routes.…”
Section: Notes On the Production Of Egyptian Blue And The Particle Sizementioning
confidence: 99%